Developing Elementary School’s Social Studies Learning Using the Monopoly Game - Nurhayati Nurhayati; Vera Rosdianti; Aprilia Sari; Nurhaliza Nurhaliza; Silvia Fransisca (International Journal Labs, 2022)
This type of research uses Classroom Action Research (CAR), this study aims to improve student learning outcomes in Social Science (IPS) learners by using monopoly game media in elementary schools. Learning media is one of the important things needed by teachers and students in the learning process, in accordance with curriculum 13 which is expected to use learning media to improve student learning outcomes, using learning using monopoly game media is very effective and can be an option for used as a medium for the teaching and learning process in the classroom, by learning using the monopoly game media students can learn while playing so that they can improve student learning outcomes by proving the results at the first meeting, namely with the highest score with a value of 70, the lowest score with a value of 40, many students who completed as many as 2 people, while many students who did not complete as many as 18 people, while the percentage of student completeness was 20%, while the second meeting was the highest score with a value of 95, the lowest score with 65 results, many students who completed as many as 17 people, while many students 3 students who did not complete, while the percentage of students' completeness was 80%.